Visualization of Social Life Cycle Assessment and Ethics Audit Outcomes in the Context of a Circular Manufacturing Ecosystem - Philipp Url; Maximilian Orgler; Rie B. Larsen; Wolfgang Vorraber (Tehnički Glasnik)
The identification and consideration of social and ethical aspects are key enablers to achieving sustainable production, including human-centrism. Existing social life cycle assessment and ethical audit methods identify relevant risks and their impacts on such complex systems. In the context of a business ecosystem, an integrated view of the assessments’ outcomes is missing. Addressing this gap, we propose an extension of the V2 value network notation. By combining economic and social sustainability aspects, the resulting holistic view creates a comprehensive visualization of the overall system. This view serves as the basis for the analysis and communication of complex socio-technical systems’ aspects. The proposed extension of the notation is presented, and its application is demonstrated by means of a case study of a platform-based circular manufacturing ecosystem that enables the reuse of assembly lines.